2016
DOI: 10.18257/raccefyn.381
|View full text |Cite
|
Sign up to set email alerts
|

Red de interacción proteína-proteína de fosfatidilinositol 4,5-bifosfato 5-fosfatasa relacionada con el síndrome de Lowe

Abstract: ResumenEl síndrome de Lowe (SL) es una enfermedad transmitida por herencia ligada al sexo, que afecta mayoritariamente a los hombres y muy ocasionalmente a las mujeres. El SL consiste en mutaciones en el gen OCRL1 que afectan el metabolismo del inositol fosfato, produciendo afecciones significativas de los ojos, el sistema nervioso y los riñones. En este estudio se construyó una red de interacción proteína-proteína para la enzima fosfatidilinositol 4,5-bifosfato 5-fosfatasa, en el software Cytoscape versión 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a study conducted in 2016, we reported that OCRL-1 is associated with multiple biological processes through protein−protein interactions. Until 2016, interactions with 27 interactors had been reported 40 and currently 63 protein−protein interactions with 57 interactors are known (Figure 1). We collected the data of all interactions for the reconstruction of the OCRL-1 protein interaction network.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In a study conducted in 2016, we reported that OCRL-1 is associated with multiple biological processes through protein−protein interactions. Until 2016, interactions with 27 interactors had been reported 40 and currently 63 protein−protein interactions with 57 interactors are known (Figure 1). We collected the data of all interactions for the reconstruction of the OCRL-1 protein interaction network.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%